Follow-up of Pastor Performance Assessment on the Quality Component of Service Supervision at HKBP District II Silindung in 2025 - Ronny Simatupang; Andar Gunawan Pasaribu (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Pastor performance assessment is an important part of efforts to improve the quality of church services. One of the main components assessed is the quality of service supervision which includes the pastor's ability to guide, supervise, and assist other servants. This study aims to examine the follow-up of the results of pastor performance assessments, especially in the aspect of service supervision, using a qualitative literature study method. By reviewing various literature related to performance management, pastoral leadership, and service supervision, it was found that effective follow-up includes ongoing training, periodic evaluations, and strengthening the mentoring system. The implementation of this follow-up is expected to increase the effectiveness of services and strengthen the role of pastors as spiritual mentors. This study provides a conceptual overview of the importance of performance development strategies based on evaluation results as a basis for service renewal in the context of the church.